Layer Poultry Farming and Egg Production Profitability Model: Basis of Layer Harvesting - Salvia, Kristine Jean; Valderama, Julius (International Journal of Arts, Sciences and Education, 2021)
The study aimed to forecast the period to harvest layers in a poultry farm. The basis of forecasting was the daily egg production data together with the Hen-Day Egg Production (HDEP) Index. The poultry farm involved in the study was a small-scale and family-owned farm intended for egg production. The farm had 1,168 Dekalb White Layers at the start of the study. All farm practices were religiously made consistent. Data on daily egg production was regularly recorded. Around 6 to 8 weeks after egg production begins, egg production is expected to reach a peak of about 90%, then gradually declines to about 65% after 12 months of lay. The poultry rule of thumb for egg production, from the highest peak to a downward trend, the 50% production rate using the HDEP index indicates the break-even point wherein the feed cost is equal to the market price of the eggs. Going below this index suggests culling the layers. On average 72 – 78 weeks, hens stopped laying eggs. The actual data on egg production together with the time-series analysis of the daily HDEP index, the period to cull layers was determined. The result shows that in the 102nd week, egg production reached 50% of the HDEP index. This indicates that layers can still optimally lay eggs beyond 78 weeks, giving 24 more weeks of egg production.